How do short videos influence users’ tourism intention? A study of key factors - Liu, Jing; Wang, Yujie; Chang, Liyan (Frontiers in Psychology, 2023)
With the acceleration of urbanization, tourism plays an increasingly important role in urban economic development. As an emerging media form, short video has incomparable advantages in publicizing tourist attractions. Based on the Stimulus-Organism-Response (SOR) model, the technology acceptance model (TAM) and flow theory, this paper constructs an influencing factor model of short videos on users’ tourism intention. Users with short video browsing habits were recruited as study participants. The results show that perceived professionalism and perceived interactivity have a significant positive impact on telepresence only; perceived enjoyment and perceived ease of use have a significant positive impact on both telepresence and flow experience; and telepresence not only has a direct and significant positive impact on tourism intention, but also has an indirect effect by significantly moderating the effect of flow experience on tourism intention. According to these influencing factors, some suggestions are put forward regarding both platform technology and video content. This study informs the construction of short video platforms and the creation of short video content, providing feasible suggestions for the promotion of tourist attractions.